Kualitas Pelayanan bagi Penyandang Tuna Netra Dinas Perpustakaan Umum dan Arsip Daerah Kota Malang - Wicaksono, Aries Samudra; Sumartono, Sumartono; Muluk, M.R. Khairul (Jurnal Ilmiah Administrasi Publik, 2020)
The City Government of Malang through the Dinas Perpustakaan Umum dan Arsip Daerah Kota Malang through the LAPOBRA service seeks to create friendly services especially for tuna netra. Over the past 4 years, the quality of the services provided can already be assessed. The goal is to find out the services provided to persons with visual impairment have met their expectations or not. The method used is a qualitative approach; type of analytic descriptive research; and the focus of research is the adjustment between PERMENPANRB 14/2017 and SERVQUAL. Based on the findings, the competence of the implementers (competence); implementing behavior (assurance); Handling of complaints, suggestions and input as well as efforts to understand the needs of visitors who are blind (understanding/ knowing the customer), as well as facilities and infrastructure (tangible), are felt to be in accordance with the expectations of blind visitors. Negative results appear on the ease of being contacted and met (access), the cause is due to the lack of interaction and assistance by service providers.